Confidentiality of wireless network data based on an information-theoretical approach - Amangeldina, A.K.; Khayrosheva, K.B. (Recent Contributions to Physics, 2020)
In modern communication systems, there is a clear separation between data encryption and error correction in the message flow. At the physical level of an open data transmission system, error correction is implemented that allows higher levels to abstract this level as an ideal bit channel. Encryption based on cryptographic principles occurs at higher levels. This separation has long been an obvious solution in most communication systems, but recently there has been an increasing interest in providing security directly at the physical level by using the properties of the basic communication channel. With this approach, security is ensured by an information-theoretic approach that does not require difficult to compute functions, as in traditional cryptography. Information and theoretical security, first introduced by Shannon and widely recognized as the most stringent security notation, is becoming increasingly attractive to many cyber-physical systems, wireless networks, distributed control systems and other applications. Nevertheless, many open questions remain for the full integration of information and theoretical security into future communication systems. This article discusses the autonomous results in the field of theoretical information security.